PET/CT imaging of differentiated and medullary thyroid carcinoma using the novel SSTR-targeting peptide (18F)SiTATE: first clinical experiences - Kunte, Sophie Carina; Wenter, Vera; Toms, Johannes; Lindner, Simon; Unterrainer, Marcus; Eilsberger, Friederike; Jurkschat, Klaus; Wängler, Carmen; Wängler, Björn; Schirrmacher, Ralf; Tiling, Maximilian W.; Sheikh, Gabriel T.; et al. (European journal of nuclear medicine and molecular imaging, 2025)
The novel 18F-labeled somatostatin receptor (SSTR)-directed radiotracer [18F]SiTATE demonstrated promising results for the imaging of various SSTR-expressing tumor types. Although thyroid carcinomas (TC) express SSTR, data on [18F]SiTATE PET/CT imaging in TC are lacking. This study explores the use of [18F]SiTATE PET/CT in a patient cohort with histologically proven TC.